Critical parameters for measuring angle of stability in natural granular materials - Arias García, Pablo Andrés (2011)
In this paper an experimental study of the measurement of stability angles for natural granular piles is presented. The critical dimensions needed for the determination of the angles according to the particle characteristics are established. The material used in the experiments was commonly coarse and fine aggregates used in road construction with a wide range of sizes. Grains were classified by size and characterized through shape factors, apparent density and compacity. The minimum size of the system necessary for measuring the angles of stability was determined depending on the type of experiment to be performed. Results are discussed in terms of the geometry of the different piles and the size of the system.